Previdência dos servidores públicos: Reflexôes em torno da proposta de instituiç\~ao da previdência complementar - Fernando Gaiger Silveira; Joana Mostafa; Marcelo Abi-Ramia; Maria Paula Gomes dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This article focuses on current aspects of the public servants` pension system in Brazil, dialoguing with the legislative proposal (PL no 1.992/2007) which aims to introduce a complementary pillar in the civil servants pension system. The proposal is been considered in Congress and will allow the adoption of a maximum threshold value for the pension benefits of retired civil servants, a value similar to that which is set to private sector workers, under the Regime Geral de Previdência Social (RGPS). The text evaluates the current model for public servants` pensions, presenting the evolution of the quantity and value of benefits; its fiscal costs; and its regressive impacts on the overall income distribution. The proposal itself is presented, as well as a simulation of prospective fiscal costs implied in the transition. The conclusion is that, if approved, the proposal will reduce the need of fiscal resources to back-up public servants` pensions in i. the future (from 2040 onwards), and opens the possibility of improving the country`s income distribution. Notwithstanding, these are only two aspects involved in the debate regarding the establishment of a new scheme for public sector pensions, which must be thoroughly analyzed elsewhere.
Keywords: H55; H75; J32; G23; 330; Altersversorgung im öffentlichen Dienst; Brasilien